Peran Bimbingan dan Konseling di Madrasah: Pendalaman Kasus Sistem Bidang Psikologi Pendidikan - Beti Malia Rahma Hidayati (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2019)
Educational – Psychology is one part of the Psychology and it is an application of Educational – psychology Science. In the Islamic school, the jobs and role of education psychologist are handed by the School Counselor. One of the junior high school in Pare often finds cases dealing with the students’ discipline. These cases mostly handed by the homeroom teacher, vice headmaster and headmaster. So far the cases found are dealing with the disciple while other cases haven’t handled maximally. The unhandled cases bring problems for the school especially the system of Islamic school. The objective of the research is to comprehend more about the existing cases by applying psychology assessment process. This process is about to apply deeper observation and interview. In other side, the role of counselor is found not maximum. As the intervention of the problem, the researcher applies the followings: 1. set a module of counseling, 2. propose a counselor, 3. create a job analysis for the counselor. The set of intervention has been done. Although the change is not maximal, the activity has been ended. However, the result is a recommendation to be followed up by the Islamic school